THE EFFECTIVENESS OF COMMUNICATIVE LANGUAGE TEACHING METHOD TO ENHANCE THE STUDENTSÃ¢â¬â¢ MOTIVATION IN INCREASING THEIR TOEFL SCORE - Martono, Eko (Language Circle: Journal of Language and Literature, 2013)
STIEPARI studentsÃ¢â¬â¢ achievement was found to have declined during 2008 - 2010. Almost all language skills were affected. One attempt to rectify the problem was the creation of a program called STIEPARI Language Course (SLC). The natures of the data in this research were quantitative and qualitative. The quantitative data were taken from the post-test TOEFL scores of 30 STIEPARI students. The 30 students were divided into 2 groups, Experimental Class and Control Class. Experimental Class was taught using Communicative Language Teaching (CLT) method in the teaching learning process; on the other hand, Control Class was taught without using CLT. The qualitative data were taken from student comments on the STIEPARI Language Course (SLC). From the t-test analysis, the result shows that there is a significant difference between the mean score of post-test of the Experimental Class and the mean score of post-test of the Control Class. This result shows that, statistically, the Communicative Language Teaching (CLT) method is an effective method to enhance studentsÃ¢â¬â¢ motivation in increasing TOEFL score. It should be mentioned, however, that TOEFL scores should be interpreted with care. To summarize studentsÃ¢â¬â¢ feedback on the STIEPARI Language Course (SLC), in general, both the Experimental Class and the Control Class learned a lot from the SLC. This comment is supported by the increase in TOEFL score.